Acute esophageal necrosis masquerading acute coronary syndrome - Ruhin Yuridullah; Varun Patel; Gabriel Melki; Janardhan Bollu (University of São Paulo, 2020)
Acute esophageal necrosis (AEN) also known as "black esophagus" or "acute necrotizing esophagus" is a rare entity characterized by striking endoscopic findings of circumferential black coloring of the esophagus. AEN most frequently seen in the distal esophagus and can extend proximally along the entire esophagus. Characteristically, the circumferential black mucosa stops abruptly at the EGJ. AEN tends to present as acute upper gastrointestinal bleeding, though other symptoms including dysphagia and epigastric pain have been described. The etiology of AEN is multifactorial including a combination of ischemic insult, mucosal barrier defect, and a backflow injury of gastric secretions. Described is a case of AEN in a patient with history of uncontrolled diabetes who presented with an atypical chest pain mimicking acute coronary syndrome with negative subsequent cardiovascular workup.